Experimental techniques in nuclear and particle physics - Tavernier, Stefaan (Springer, 2013)
Based on a course taught for years to students in both nuclear and biomedical engineering, this book first introduces the structure of matter at the subatomic scale before it covers the experimental aspects of nuclear and particle physics.